Investigating autonomy of Malaysian ESL learners: a comparison between public and private universities - Thang, Siew Ming (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2009)
The concept of autonomy in the context of language education in Europe had focused on the importance of personal autonomy. It was only recently that cultural influences were taken into consideration in interpreting autonomy. Studies on undergraduates learning ESL (English as a Second Language) in public universities in Malaysia revealed that the students were basically teacher-centred and lacked personal autonomy. These findings are in line with research findings from many other Asian contexts. This study investigated whether this phenomenon applied to students at a private university in Malaysia. A quantitative approach in the form of questionnaires was used in this study. The findings revealed that generally learners from both public and private universities preferred a more teacher-centred approach. However, although the majority of the students from the three public universities still maintained this position in their choice of strategies in learning, the students in the private university seemed to have moved towards a more autonomous position.